High-cell-density fermentation of Saccharomyces cerevisiae for the optimisation of mead production - Pereira, Ana Paula (2014)
Mead is a traditional drink that contains 8%e18% (v/v) of ethanol, resulting from the alcoholic fermentation of diluted honey by yeasts. Mead fermentation is a time-consuming process and the quality of the final product is highly variable. Therefore, the present investigation had two main objectives: first, to determine the adequate inoculum size of two commercial wine-making strains of Saccharomyces cerevisiae for the optimisation of mead fermentation; and second, to determine if an increase in yeast pitching rates in batch fermentations altered the resulting aroma profiles. Minor differences were detected in the growth kinetics between the two strains at the lowest pitching rate. With increasing pitching rates net growth of the strain ICV D47 progressively decreased, whereas for the QA23 the increasing inoculum size had no influence on its net growth. The time required to reach the same stage of fermentation ranged from 24 to 96 h depending on the inoculum size. The final aroma composition was dependent on the yeast strain and inoculum size. Fourteen of the twenty-seven volatile compounds quantified could contribute to mead aroma and flavour because their concentrations rose above their respective thresholds. The formation of these compounds was particularly pronounced at low pitching rates, except in mead fermented by strain ICV D47, at 106 CFUs/mL. The esters isoamyl acetate, ethyl octanoate and ethyl hexanoate were the major powerful odourants found in the meads. The results obtained in this study demonstrate that yeast strain and inoculum size can favourably impact mead’s flavour and aroma profiles.